Development of CMOS dosimetry in proton minibeams for enhanced QA and primary standard absorbed dose calorimetry. (9th March 2023) - Flynn, Samuel; Allport, Philip; De Marzi, Ludovic; Green, Stuart; Homer, Michael; Lee, Nigel; Ortiz, Ramon; Patriarca, Annalisa; Prezado, Yolanda; Thomas, Russell; Price, Tony
Abstract: Performing accurate and reliable dosimetry in spatially fractionated beams remains a significant challenge due to the steep dose gradients and microscopic scale of features. This results in many conventional detectors and instrumentation being unsuitable for online dosimetry, necessitating frequent offline validation using radiochromic film. In this study, the use of a Complementary Metal-Oxide-Semiconductor (CMOS) detector for evaluation of relative real-time dosimetry of proton minibeam radiation therapy (pMBRT) was investigated. The linearity of the CMOS detector was investigated by varying the proton beam current, with a comparison to a PTW 34001 Roos ionisation chamber used to carry out an independent check. It was found that the relative peaks and valleys of the pMBRT beam could be measured, with results comparable to EBT3XD film. The high sensitivity of the CMOS detector meant it was able to measure dose profiles from peak to valley regions, something not possible with the EBT3XD. The CMOS detector was compared to the treatment delivery log files, with correlation in beam position seen as the beam is scanned along each slit, but not across; and agreement in beam intensity, with the CMOS detector able to observe beam interruptions. Lastly, the CMOS detector was used in conjunction with the NPL primary-standard proton calorimeter (NPL PSPC) for a preliminary study on combining the NPL PSPC with high resolution temporal information about the incident pMBRT beam. The ultimate aim of this approach is to facilitate detailed thermal modelling to reduce the overall uncertainty in the absolute dose measured from the calorimeter. In these experiments, saturation in the CMOS pixels prevented further thermal modelling of the radiation induced heat flow, however the instantaneous dose rate was observed to be comparable with the predicted NPL PSPC response obtained by masking the CMOS detector.